Workshop Pengembangan Media Pembelajaran Interaktif Kreatif Dalam Melaksanakan Tri Dharma Perguruan Tinggi Di SMK Widya Nusantara Bekas - Herlawati, Herlawati; Khasanah, Fata Nidaul; Sari, Rafika; Atika, Prima Dina; Sugiyatno, Sugiyatno; Handayanto, Rahmadya Trias; Samsiana, Seta (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
SMK Widya Nusantara is one of the best vocational schools in the city of Bekasi whose students and teachers have the hope of creating independent and characterized people who are based on faith and piety. The main element to be able to realize the hopes of the Vocational High School is that it has collaborated with universities in training activities and improving knowledge from various fields, so that they can compete in the era of globalization. Currently strengthening the competence of students and teachers is the main thing, because later they will be able to compete with other developed countries. To strengthen these competencies, training and simulations on the development of creative interactive learning media were carried out at SMK Widya Nusantara. It begins with a survey, then it is analyzed and finally the training activities are carried out. The result of this community service is that students and teachers are able to understand the creation of creative interactive learning media such as the use of a mentimeter, classroom google, youtube and the use of powerpoint, examples and their application, so that students and teachers have special knowledge about this which is useful for increasing competence and global competition.